Vocabulary Knowledge, Cognitive Linguistic Skills, and Their Relation with Speaking Proficiency of EFL University Students - Ahmed, Ayat Hussein; Yahya, Nagham Q. (Journal of Tikrit University for Humanities, 2025)
Vocabulary knowledge and cognitive linguistic abilities are pivotal elements of oral communicative competence in English as a Foreign Language (Henceforth, EFL) setting. This correlational study aims to examine the interrelationship between vocabulary knowledge assessed through both breadth (the extent of vocabulary size) and depth (the richness and quality of word knowledge)-and cognitive linguistic skills, including working memory, attention control, and metacognitive awareness, in relation to speaking proficiency among Iraqi EFL learners. The study sample consists of 180 second -year undergraduate students from the College of Education for Humanities at the University of Tikrit during the academic year (2024–2025). Stratified random sampling is employed to ensure gender representation in the sample. A comprehensive set of instruments is utilized to measure the target constructs: a vocabulary test (evaluating both breadth and depth), a cognitive skills questionnaire, and a structured speaking interview based on an IELTS-inspired rubric that assessed fluency, accuracy, lexical diversity, and coherence. The findings reveals that vocabulary depth was a significant predictor of speaking proficiency (r = 0.72, p < 0.01), highlighting the critical role of collocations, word associations, and semantic richness in facilitating oral fluency. Vocabulary breadth was moderately correlated with speaking proficiency (r = 0.54, p < 0.01), indicating its complementary influence on oral expression. Among the cognitive variables, working memory (r = 0.65, p < 0.01) and attention control (r = 0.58, p < 0.01) demonstrated significant correlations with speaking performance, suggesting that cognitive processing efficiency is essential for real-time language production.